Applying Systems Thinking via Systemigrams™ for Defining the Body of Knowledge and Curriculum to Advance Systems Engineering (BKCASE) Project - and Squires, Alice; Pyster, Art; Sauser, Brian; Olwell, David; Enck, Stephanie; Gelosh, Don; Anthony, Jim (INCOSE International Symposium, 2010)
Systems thinking is commonly accepted as the backbone of a successful systems engineering approach. As such, the Body of Knowledge and Curriculum to Advance Systems Engineering (BKCASE) team chose to leverage a systems thinking based tool, called Systemitool, to describe our project to the vast audience that would potentially become involved directly or indirectly in the success of the project. This paper describes the process and steps used by the authors and the BKCASE team to develop the project's systemic diagram, or Systemigram™, and the story behind the project, the products, and the vision of the BKCASE project. The goal of the paper is to provide guidance so that readers can leverage the lessons learned from this effort to successfully develop their own project definitions and stories.